Model Penentuan Bond Yield dengan Faktor Internal dan Eksternal Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Dasman, Sunita; Widiastuti, Widiastuti (Jurnal Akuntansi Bisnis Pelita Bangsa, 2024)
Bondholders expect bond yields in their investments in bond instruments. This study aims to analyze the company's internal factors which include liquidity, profitability and leverage on bond yields in manufacturing companies that issue bonds in the period 2018-2021. Purposive sampling method was used in this study and obtained 12 manufacturing companies during the study period. Multiple linear regression was used to obtain the impact of internal and external factors on bond yields. The increase in the company's liquidity and profitability indicates a decrease in bond yields. Meanwhile, the increase in leverage indicates an increase in bond yields. Increased leverage can increase bond yields. External factors do not show an impact on bond yield.